Poly(3-hexylthiophene)–graphene composite-based aligned nanofibers for high-performance field effect transistors1. Issue 17 (7th May 2015) - Lin, Chih-Jung; Liu, Cheng-Liang; Chen, Wen-Chang
<x xml:space="preserve">Abstract</x> A high-performance FET with a maximum mobility of 1.82 cm2 V−1 s−1 was fabricated from aligned electrospun P3HT–graphene composite nanofibers.